The Urea Cycle Disorders (UCD): A Case Report - Islam, Md Tariqul; Islam, Md Imnul; Hoque, Seikh Azimul; Saleh, Abu Sadat Md; Parvin, Zobayda; Saha, Narayan Chandra (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v36i1.13039 Bangladesh J Child Health 2012; Vol 36 (1): 46-48